2020
DOI: 10.1371/journal.pone.0237496
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of quantifying change in immune white cells in abdominal adipose tissue in response to an immune modulator in clinical obesity

Abstract: Background Obesity is often associated with inflammation in adipose tissue (AT) with release of mediators of atherogenesis. We postulated that it would be feasible to collect sufficient abdominal AT to quantify changes in a broad array of adaptive and innate mononuclear white cells in obese non-diabetic adults in response to a dipeptidyl protease inhibitor (DPP4i), known to inhibit activation of immune white cells. Methods Adults 18-55 years-of-age were screened for abdominal obesity and insulin resistance or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
(84 reference statements)
0
3
1
Order By: Relevance
“…A few studies have reported that ARBs and DPP‐4 inhibitors reduce inflammation markers in individuals with type 1 diabetes or type 2 diabetes 2–4,8–10 . There were no clear reductions in any of the measured markers during treatment with these drugs in our study, although the decrease in IL‐18 and IP‐10 observed after 4 weeks of treatment with linagliptin was observed in a prior study with DPP‐4 inhibitors 10,30 . The contrasting findings may be attributable to the short treatment period in ROTATE or because we measured the biomarkers in the systemic circulation, which is not always a proper reflection of the inflammatory marker concentration within tissues or organs 31 .…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…A few studies have reported that ARBs and DPP‐4 inhibitors reduce inflammation markers in individuals with type 1 diabetes or type 2 diabetes 2–4,8–10 . There were no clear reductions in any of the measured markers during treatment with these drugs in our study, although the decrease in IL‐18 and IP‐10 observed after 4 weeks of treatment with linagliptin was observed in a prior study with DPP‐4 inhibitors 10,30 . The contrasting findings may be attributable to the short treatment period in ROTATE or because we measured the biomarkers in the systemic circulation, which is not always a proper reflection of the inflammatory marker concentration within tissues or organs 31 .…”
Section: Discussioncontrasting
confidence: 75%
“…2-4,8-10 There were no clear reductions in any of the measured markers during treatment with these drugs in our study, although the decrease in IL-18 and IP-10 observed after 4 weeks of treatment with linagliptin was observed in a prior study with DPP-4 inhibitors. 10,30 The contrasting findings may be attributable to the short treatment period in ROTATE or because we measured the biomarkers in the systemic circulation, which is not always a proper reflection of the inflammatory marker concentration within tissues or organs. 31 Unfortunately, we were unable to assess changes of the inflammatory markers in urine because these data were not available.…”
Section: Discussionmentioning
confidence: 99%
“…The following established flow cytometric gating strategies based on previous publications [ 42 47 ] were used to quantify the different immune cell sub-populations using the eight-color BD FACSCANTO analyzer, and data were acquired using BD FACSDiva software (BD Bioscience, San Jose, CA): CD45+, CD14+, CD163- for M1 macrophages, CD45+, CD14+, CD163+ for M2 macrophages, CD45+, CD4+, CD25+, CD127 low for regulatory T cells (Treg), CD45+, CD4+, CD25+, CD127 high for T effector cells (Teff). The total number of M1, M2, Treg, Teff subsets were quantified using FlowJo version 10 software (TreeStar Ashland OR) and were normalized to grams of AT collected or per milliliter of blood collected, respectively, as previously described [ 44 , 47 49 ]. Gating strategy and flow cytometry of a representative sample are shown in Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Novel regulators of ILC2 function such as GITR ( 20 ) and DR3 ( 28 ) provide clear avenues for the amelioration of insulin resistance and establishing glucose tolerance in obese individuals. In vivo drug treatment has been shown to regulate human adipose ILC2 populations ( 198 ). Overall, more immunotherapeutic strategies need to be adapted to complex diseases such as T2DM as the presence of immune dysregulation is a key driver in their development and pathogenesis.…”
Section: Novel Targets For Amelioration Of T2dmmentioning
confidence: 99%